PERFIL DOS GESTORES DAS ESCOLAS PÚBLICAS MUNICIPAIS DE SÃO JOSÉ DE RIBAMAR - MA - Silva, Jorge Antonio Rocha da (2014)
This dissertative study, is linked to the Line of Research, State and Education Management Research Group Basic Education Policies of the Graduate Program in Education at the Federal University of Maranhão. It has as its central theme the school management, particularly regarding to the profile of managers of municipal schools of São José de Ribamar in Maranhão. It´s part of the effort to better understand the relationship between the macro context of public policymaking - the state and capitalism, and its impact in determining priorities contemplated in educational policies adopted in Brazil since the 1990s. The Study demarcates the inter-relationships between the global with the local context with emphasis on the strategies of reorganization of the capitalist world economy, the adoption of globalization, neo-liberal principles and the scientifictechnical progress that boosted the productive restructuring, imposing changes in management and organization of work processes. It´s reflected on the fiscal adjustment in the context of state reform, and in this context on educational reform. The qualitative research grounded in dialectical historical materialism for larger categories of democratization, school management, professional profile understanding, advancing beyond the limits imposed by educational policy, formulated in the context of capitalist society. It Includes four steps; bibliographical research, Documental research and field research. The literature supported the theoretical literature on administration and management books, theses, articles from authors such as: Antunes (1999), Chesnais (1998), Cabral Neto, (2009), Frigotto (2000) and Oliveira (2009), Gold and Oliveira (1999), among others, makes a raid on theoretical conceptions of administration, public administration school, highlighting the managerial and democratic perspective from its principles and conceptual basis in order to identify the influences exerted in the duties of managers. The documental research included the LDB, PNE, Programs, Projects, Resolutions, benchmarks and other legal instruments which provides for the design of public school management, principles and duties. The empirical research used as a tool for collecting semi-structured with opened and closed questions, applied to 51 managers Municipal Education Network of São José de Ribamar questionnaire data. Also used the instrument to measure context SAEB / Proof of Brazil in 2011, applied by the Institute of Educational Studies Teixeira - INEP / MEC. The study stated that municipal follows researched hybrid management model, since it meets the national guidelines now printing complementary conceptions, sometimes antagonistic, blending both orientations more economic nature, in tune with the principles and practices of managerial public administration, with more progressive nature guidelines guided by benchmarks of participatory democratic management, and consistent with the critical theories that posit a conception of education understood as a form of social emancipation.